2021
DOI: 10.3390/coatings11030307
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Solution Deposition of La-Substituted BiFe0.5Sc0.5O3 Perovskite Thin Films on Different Substrates

Abstract: In the present work, polycrystalline Bi0.67La0.33Fe0.5Sc0.5O3 thin films were synthesized using a simple and cost-effective chemical solution deposition process employing the spin coating technique. In order to check the feasibility of the fabrication of thin films on various types of substrates, the films were deposited on Pt-coated silicon, silicon, sapphire, corundum, fused silica and glass. Based on the results of thermogravimetric analysis of precursor and thermal stability study, it was determined that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Therefore, two-dimensional (2D) ferroelectric thin films with smooth surfaces and stable polarization are promising for the development of electronic applications. For example, Griesiute et al obtained La-substituted BiFe 0.5 Sc 0.5 O 3 perovskite thin films with different crystal structures and roughness through fabricating films on different substrates [6]. Similarly, Magalhaes et al grew Na 0.5 Bi 0.5 TiO 3 (NBT)-based epitaxial films on different single crystalline substrates and found that the films showed excellent ferroelectric and dielectric properties (Pr = 1.2 µC/cm 2 , Ec = 58 kV/cm for 1 µm-NBT-BT films), and the roughness of films strongly was found to depend on film thickness [7].…”
mentioning
confidence: 99%
“…Therefore, two-dimensional (2D) ferroelectric thin films with smooth surfaces and stable polarization are promising for the development of electronic applications. For example, Griesiute et al obtained La-substituted BiFe 0.5 Sc 0.5 O 3 perovskite thin films with different crystal structures and roughness through fabricating films on different substrates [6]. Similarly, Magalhaes et al grew Na 0.5 Bi 0.5 TiO 3 (NBT)-based epitaxial films on different single crystalline substrates and found that the films showed excellent ferroelectric and dielectric properties (Pr = 1.2 µC/cm 2 , Ec = 58 kV/cm for 1 µm-NBT-BT films), and the roughness of films strongly was found to depend on film thickness [7].…”
mentioning
confidence: 99%